Hubungan Pengetahuan, Sikap dan Pola Penggunaan Earphone dengan Kejadian Tinnitus pada Siswa SMA Negeri 7 Kota Kupang - Freitas, Apendita Joice; Christiani Berek, Noorce; Romeo, Petrus (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
The development of telecom and audiovisiual technology has increased rapidly with the discovery of various portable devices, one of which is earphones. The problem is that improper use of earphones can cause various hearing problems, one of which is tinnitus. It is known that 9 out of 10 students of SMA Negeri 7 Kupang City experience tinnitus. This study aims to determine the relationship between knowledge, attitudes and patterns of earphone use with the incidence of tinnitus in students of SMA Negeri 7 Kupang City. This type of research is quantitative research with a cross-sectional approach. The total sample of 75 students was selected by the consecutive sampling technique. Each of the variables was studied with the Chi Square test to determine the relationship with the tinnitus incidence variable. The results of the statistical test showed the relationship of knowledge of earphone use with the incidence of tinnitus p = 0.004 (< 0.05), the relationship of earphone use attitudes with the incidence of tinnitus p = 0.015 (< 0.05), and the relationship of earphone use patterns with the incidence of tinnitus p = 0.000 (<0.05). In conclusion, there is a relationship between knowledge, attitudes and patterns of earphone use with the incidence of tinnitus in students of SMA Negeri 7 Kupang City. Keywords: tinntius,earphone, knowledge, attitudes, patterns of use